Keutamaan Bersedekah Sebagai Upaya Meningkatkan Kesehatan Mental - Zhila Jannati (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2021)
Alms is one of the worship commanded by Allah swt. and recommended by the Messenger of Allah who by doing so humans will get a very beautiful reward from Him. The form of gratitude for all that Allah swt has given. Giving to humans can be realized by carrying out alms, both material and non-material alms. In addition, alms is one way that can be taken so that individuals can obtain a healthy mental. The purpose of this paper is to provide an understanding to each individual regarding the mental health of individuals in giving alms, with this understanding it is hoped that each individual will be happy and continue to give alms while Allah swt. breath to him on this earth. The results of this study are that in addition to obtaining rewards from Allah swt., alms can also make individuals mentally healthy where individuals can achieve happiness within themselves and can also create happiness for others. In addition, by giving charity, a person can achieve harmony of the functions of his soul, can create a sense of happiness and health, can avoid mental disorders, can face the challenges and trials of life well, can be positive with oneself and others and can accept what other people are